Fungal symbiont community and absence of detectable mycangia in invasive Euplatypus ambrosia beetles - Rodrigues, Andre [UNESP]; Johnson, Andrew J.; Joseph, Ross A.; Li, You; Keyhani, Nemat O.; Stanley, Edward L.; Weiss, Benjamin; Kaltenpoth, Martin; Smith, Matthew E.; Hulcr, Jiri (Springer Nature, 2023)
Platypodinae ambrosia beetles depend on mutualistic fungi for food, and both partners cooperate in colonizing dead trees. The fungi are transported in specialized structures (mycangia), but the location of mycangia is unknown in many platypodine species. One species with elusive mycangia is Euplatypus parallelus, widespread in the Americas, and recently invasive worldwide. Drawing on knowledge about other ambrosia beetles, we predict that the mycangia may be either internal in the head, internal or external within the prothorax, or the symbiont is carried within the hindgut. We attempted detection using X-ray computed tomography, Fluorescence In Situ Hybridization and histology. For method validation and comparison we used Euplatypus compositus, a related species with pronotal mycangia. Despite routine isolation of the ambrosia fungi from both sexes, no consistent mycangia-like structures were found anywhere within E. parallelus. Both Euplatypus species yielded a diverse fungal community on different body parts, but the most consistent associate of both beetle species, and the most likely nutritional mutualist, is Raffaelea xyleborini. A notable discovery is that during dispersal in both species, females had their hindgut filled with a mass of tightly packed yeasts, mostly an unknown Starmera species. The function of this yeast cache is not known. Our results showed that both Euplatypus species are associated with the same fungus, but E. parallelus either does not have mycangia or we failed to locate them. This study adds to the growing evidence that Platypodinae beetles have coevolved with members of the genus Raffaelea and that they are promiscuous at the genus level.
Keywords: Fungal diversity; Fungus transport; Mutualists; Ophiostomatales; Platypodinae